Mecanismos de defesa contra herbivoria em espécies vegetais do cerrado: o papel do silício, nectários extraflorais e látex - Oliveira, Flávio Rodrigues (2004)
Defensive mechanisms in plant species have been received great attention in ecological studies. However, low importance is giving to Silicon as a defensive agent in plants. In the present study we investigated defensive strategies against herbivory in Brazilian Savannah, related to Chemical defenses (foliar Silicon content) and the presence or absence of biotic defenses (extrafloral nectaries, EFNs). We sampled 15 tree species were sampled (ffve with NEFs and 10 without these glands) and investigated Silicon content in the tissue and foliar herbivory. The results suggested that Silicon is an effective agent to reduce herbivores action of in such species that accumulate this element. Plants bearing EFNs do not accumulate Silicon however, the presence of these EFNs constitutes an efficient defense against herbivory in the Brazilian Savannah. We suggest that the plants do not use only one defensive mechanism, all the time and we can not to point one as more effective in relation to the others. The selection for the defensive mechanism is subject of specifíc ecological pressures, not being able to one to say, therefore, that one choice is superior or more advantageous than other.